Experimental investigation of turbulence effects on sediment pickup rate in open channel flows - Adel Emadzadeh (2014)
Laboratory experiments were conducted to measure the sediment pickup rate in open-channel flows with and without externally-generated turbulence. Experiments were conducted under four kinds of flow conditions: (1) uniform flow without any obstruction, (2) flow obstructed by a horizontal pipe placed above the bed, (3) flow obstructed by a vertical pipe located at the centerline of the channel and (4) flow over two-dimensional fixed dunes. Three uniform sediment particles with D50 = 0.23, 0.44 and 0.86 mm were used for pickup experiments and the flow velocity and turbulence were measured by a 3D down-looking Acoustic Doppler Velocimeter (ADV). Dimensional analyses were performed for all the experimental data resulting in empirical pickup functions based on both near-bed and bulk flow parameters. For the experiments under the undisturbed uniform flow conditions, the pickup rate could be well represented by both near-bed and depth averaged flow parameters. However, in nonuniform flows, the pickup function was proposed based only on bulk flow parameters.